Understanding the Influence of Design Factors and Volumetrics on Moisture Susceptibility of Hot-Mix Asphalt - Shaikh S.; Tiwari A.; Gupta A. (My University, 2025)
This study evaluated the individual and cumulative impact of different design factors on moisture damage of hot-mix asphalt (HMA) using the modified Lottman test. This study considered five different types of design aggregate gradations (DAG), three binder types, and three levels of compactive effort. To evaluate the significance of the influential factors that affected the moisture sensitivity of the mix, statistical analysis was performed. This study also investigated the influence of volumetric parameters of the bituminous mixes on moisture damage. The correlation of different design factors and various volumetric parameters with the tensile strength ratio (TSR) was further investigated through analysis using the Pearson correlation coefficient. The need for this investigation arises from the scarcity of comprehensive studies examining the individual and combined effects of various factors and the impact of volumetric parameters on moisture susceptibility. Additionally, linear regression models were developed to predict TSR based on the design factors and volumetric parameters considered in the study. The final model showed a close fit, with low mean absolute percentage error (MAPE=0.931) and a good coefficient of determination (R2=0.752). Moreover, based on the tested mixtures, the study establishes a threshold value of dry indirect tensile strength (ITSdry=750 kPa) and wet indirect tensile strength (ITSwet=650 kPa), along with TSR (= 0.85). © 2024 American Society of Civil Engineers.